2007
DOI: 10.1091/mbc.e07-01-0080
|View full text |Cite
|
Sign up to set email alerts
|

Rab6 Regulates Both ZW10/RINT-1– and Conserved Oligomeric Golgi Complex-dependent Golgi Trafficking and Homeostasis

Abstract: We used multiple approaches to investigate the role of Rab6 relative to Zeste White 10 (ZW10), a mitotic checkpoint protein implicated in Golgi/endoplasmic reticulum (ER) trafficking/transport, and conserved oligomeric Golgi (COG) complex, a putative tether in retrograde, intra-Golgi trafficking. ZW10 depletion resulted in a central, disconnected cluster of Golgi elements and inhibition of ERGIC53 and Golgi enzyme recycling to ER. Small interfering RNA (siRNA) against RINT-1, a protein linker between ZW10 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
146
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(159 citation statements)
references
References 53 publications
13
146
0
Order By: Relevance
“…Several studies demonstrated that RINT1 is involved in ER-Golgi trafficking in vitro. 16,17,[19][20][21] Lin et al 19 associated the observed mitotic defects with Golgi dispersion and centrosome amplification. We demonstrated that centrosome amplification in MEFs is not correlated with mitotic defects and in NSC is not detected at all.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies demonstrated that RINT1 is involved in ER-Golgi trafficking in vitro. 16,17,[19][20][21] Lin et al 19 associated the observed mitotic defects with Golgi dispersion and centrosome amplification. We demonstrated that centrosome amplification in MEFs is not correlated with mitotic defects and in NSC is not detected at all.…”
Section: Resultsmentioning
confidence: 99%
“…16,58 RINT1 was shown to be also involved in the more specific Rab6-dependent recycling pathway from the Golgi to the ER. 20 Disruption of the balance of the bi-directional ER/Golgi transport was shown to trigger Golgi fragmentation followed by ER stress. 1,55 Complementary to former RINT1 studies where ER stress was not reported 16,17,19 here we postulate that in our model, Rint1 deficiency generates ER/Golgi imbalance leading to Golgi apparatus fragmentation, induction of ER stress and ultimately cell death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S1B). Another dynein regulator, ZW10, is also required to maintain the structure of the Golgi complex (Hirose et al, 2004;Sun et al, 2007). In cells depleted of ZW10, the Golgi complex fragmented into very short tubules that remained in a patch close to the cell centre (supplementary material Fig.…”
Section: Both Nde1 and Ndel1 Are Important For Maintaining Organelle mentioning
confidence: 99%
“…To test this idea, we focused attention on the distribution of ERGIC-53. ERGIC-53 principally cycles between the ERGIC and ER in a COPI-dependent, but Rab6-independent manner (Girod et al, 1999;Nufer et al, 2002;Sun et al, 2007;White et al, 1999), thereby this protein is a good marker for the recycling pathway, although its loss does not block COPII assembly at ER exit sites (Mitrovik et al, 2008).Although the overall staining intensity of ERGIC-53 was substantially increased in syntaxin-18-depleted cells (Fig. 5A, left column), this was not due to its upregulation, as demonstrated by immunoblotting (supplementary material Fig.…”
mentioning
confidence: 99%